Last of the sandwalkers - Hosler, Jay
When field scientist Lucy defies the law of her safe but authoritarian home on an oasis by leading a team of researchers into the desert to learn about the greater world, what she finds will change everything, beginning with the knowledge that beetles are not the only living creatures.
Chiefly illustrations.
Keywords: Beetles; Scientific expeditions; Adventure and adventurers; Cartoons and comics; Juvenile fiction -- Comics & Graphic Novels -- General; Juvenile fiction -- Science Fiction; Juvenile fiction -- Animals -- Insects, Spiders, etc; Graphic novels; Comic books, strips, etc; Fiction; Juvenile works